Mechanism and application prospect of ferroptosis inhibitors in improving osteoporosis - Wang, Jing; Chen, TingRui; Gao, Fei (Frontiers in Endocrinology, 2024)
Osteoporosis, a prevalent bone metabolic disorder, has emerged as a pressing global public health concern. Recent studies have illuminated a crucial link between ferroptosis and the pathogenesis of osteoporosis. Nevertheless, the intricate mechanisms underlying the role of ferroptosis in this condition remain largely unexplored. Therefore, this article comprehensively reviews the regulatory mechanisms of ferroptosis and the modulating effects on the development and progression of osteoporosis, as reported in recent years. Furthermore, this review summarizes the current state of the interventional strategies employed by both Western medicines and traditional Chinese medicines (TCMs) in addressing osteoporosis. This review aims to uncover potential novel avenues for the prevention and control of osteoporosis by synthesizing the modes of action and clinical efficacy of these therapeutic modalities.